La débil integración de lo ambiental en el Perú - Alcalde, Gonzalo (Pontificia Universidad Católica del Perú, 2025)
In 21st-century Peru, decisions about development —even at high levels of government— still do not fully consider the environmental dimension. This occurs despite progress in environmental institutions since the 1990s, and despite official discourses and instruments that are ostensibly aligned with sustainable development. This omission has been especially evident at critical moments in the last decade, when existing environmental regulation has been weakened. This essay proposes that the policy coherence framework for sustainable development (PCSD) —still rarely used domestically— makes it possible to identify different points where the integration of environmental issues into development decisions needs to be strengthened. In this sense, it is argued that the most urgent pending agenda refers not only to the environmental policy space, but also to points in the policy process where coherence between the major policy spaces (economic, social, environmental) and coherence between national decisions and the country’s international commitments can be ensured.

En el Perú del siglo XXI, las decisiones sobre desarrollo —incluso las de alto nivel— aún no consideran plenamente la dimensión ambiental. Esto ocurre a pesar de los avances en la institucionalidad ambiental desde los años noventa, y no obstante los discursos e instrumentos oficiales que están ostensiblemente alineados con el desarrollo sostenible. La omisión ha sido especialmente evidente en momentos críticos de la última década, donde se ha llegado a debilitar la regulación ambiental existente. Este ensayo propone que el marco de coherencia de políticas para el desarrollo sostenible (CPDS) —poco utilizado aún en el ámbito nacional— permite identificar distintos puntos donde hace falta fortalecer la integración de lo ambiental en las decisiones sobre el desarrollo. En este sentido, se argumenta que la agenda pendiente más urgente no solo se refiere al espacio de las políticas ambientales, sino también a los puntos del proceso de políticas donde se puede asegurar la coherencia entre los grandes espacios de políticas (económica, social, ambiental) y la coherencia entre las decisiones nacionales y los compromisos internacionales del país.
Weak environmental integration in Peru
Keywords: Sustainable development; Policy coherence; Environmental policy; Policy reform; 2030 Agenda; Desarrollo sostenible; Coherencia de políticas; Política ambiental; Reformas de políticas; Agenda 2030; https://purl.org/pe-repo/ocde/ford#5.04.00